The Influence of ROA, ROE, FDR, and BOPO on Capital Adequacy in Sharia Commercial Banks in Indonesia 2018 - 2022 - Susilowati, Susilowati; Amalia, Naini (Insight Management and Business (IMB), 2024)
A bank health assessment is needed to find out whether the bank's condition is unhealthy, Company performance can take appropriate steps to handle it. The choice of CAR (Capital Adequacy Ratio) as the dependent variable is because according to Bank Indonesia, the Capital Adequacy Ratio is the most important indicator in maintaining the level of bank health. This research aims to analyze the influence of ROA, ROE, FDR, BOPO and inflation on capital adequacy as measured by the Capital Adequacy Ratio (CAR) in Sharia Commercial Banks in Indonesia. The data used is secondary data and the method used is multiple linear regression analysis using the SPSS version 27 program to obtain results regarding the relationship between one variable and another. The sampling method used in this research is purposive sampling with the research sample consisting of 10 Sharia Commercial Banks in Indonesia for 5 periods from 2018-2022. The analysis results show that ROA has a effect on CAR, ROE has effect on CAR, FDR has a effect on CAR, and BOPO has no effect on CAR.